A Case of Giant Subcutaneous Bronchogenic Cyst - Nakao, Takako; Katayama, Misato; Kino, Hiromi; Hanaoka, Nobuharu; Ueda, Koichi (Archives of Clinical and Medical Case Reports, 2020)
Bronchogenic cysts are congenital anomalies that are typically found in the mediastinum or within the lung. Subcutaneous and cutaneous lesions are rare and most likely represent ectopic or displaced mesenchyme during early development. A 59-year-old male was referred by a respiratory surgeon for a giant tumor in the pre-sternal region. The tumor was elastic soft, round and mobile; however, the base was fixed to the sternal area. A CT scan showed round and cystic lesion of 14.7 × 12 × 8.0 cm in size and localized on the sternum. We began the tumor resection while draining fluid from the cyst slowly to maintain adequate tension on the surface on the cyst. We carefully dissected the surrounding tissue from the cyst to avoid rupture, and excised the cyst completely. There was no connection between the cyst and thorax. Unclear yellowish and seromucous fluid totaling 70 ml was drained. We closed the surgical wound inserting a drain tube after irrigation. Histopathological examinations revealed benign ciliated columnar epithelium with goblet cells located in the dermis and hypodermis, and partly lined by keratinizing stratified squamous epithelium. Glandular acini and smooth muscle exist within the cyst. The diagnosis was subcutaneous bronchogenic cyst. In this report, we describe an operation to treat a giant subcutaneous bronchogenic cyst 15 × 12 cm in size.